2016
DOI: 10.1038/tpj.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Gefitinib toxicity in advanced non-small cell lung cancer (NSCLC): a pharmacogenomic study of metabolic enzymes and transporters

Abstract: Skin rash, diarrhea and hepatotoxicity are the most common toxicities of Gefitinib, an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor. The present study investigated the effects of genetic polymorphisms of drug target, metabolizing enzymes and transporters on Gefitinib toxicities. Thirty single-nucleotide polymorphisms, including EGFR, cytochromes P450 and ATP-binding cassette (ABC), were genotyped by matrix-assisted laser desorption/ionization time-of-flight platform in 59 non-small cell lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 33 publications
3
59
1
Order By: Relevance
“…44 In our previous study, ABCB1 polymorphism was found to be correlated with Gefitinib skin toxicity. 45 We, for the first time, examined the association of ABCB1 rs2235040 CT genotype with periorbital oedema in GIST patients treated with Imatinib, finding it a valuable protective factor in predicting this toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…44 In our previous study, ABCB1 polymorphism was found to be correlated with Gefitinib skin toxicity. 45 We, for the first time, examined the association of ABCB1 rs2235040 CT genotype with periorbital oedema in GIST patients treated with Imatinib, finding it a valuable protective factor in predicting this toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the relationship between the genotype of the metabolizing enzyme/transporter and PKs or toxicity of EGFR TKIs . ABCB1 rs1128 503 or ABCG2 rs2231 142 SNPs were found to be related to increased gefitinib adverse events, such as skin rash and/or diarrhoea .…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports regarding gefitinib therapy and ABCG2 C421A, it was unclear whether the polymorphisms were associated with clinical efficacy. Some previous studies showed that gefitinib is associated with a higher frequency of adverse effects in wild-type versus variant-type ABCG2 C421A (35)(36)(37). Meanwhile, Cusatis et al reported that patients with reduced ABCG2 activity due to genetic variants are at increased risk of diarrhea on gefitinib treatment (35).…”
Section: Discussionmentioning
confidence: 99%